INFORMATION LITERACY, DIGITAL LITERACY, AND BEHAVIOURAL INTENTION: STUDY OF DIGITAL TECHNOLOGY ADOPTION BY CIVIL SERVANTS IN GOVERNMENT WORKPLACES - Ammy Rakhmiati; Suwandi Sumartias; Priyo Subekti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The low level of digital technology adoption by local governments to support public services and performance prompted this study. This study employs the Technology Acceptance Model (TAM) to evaluate how information literacy and digital literacy influence civil servants’ behavioral intentions regarding the use of digital technology in the workplace. A probability sample of 258 civil servants was surveyed for the quantitative investigation. PLS-SEM was used to analyze the data. The results indicate that information literacy and digital literacy have a significant positive effect on perceived ease of use, whereas only information literacy has a direct and significant effect on perceived usefulness. Furthermore, perceived ease of use strongly influences perceived usefulness and enhances civil servants’ behavioral intentions to adopt digital technology. This study concludes that civil servants’ information literacy and digital literacy play a crucial role in driving the adoption of digital technology within the government workplace. Strengthening information literacy and digital literacy integrated with user-friendly technology system design is essential to foster sustainable technology use and improve public service performance.